Perancangan Sistem Penggajian Tenaga Harian Lepas pada PT Srikandi Nusantara Jaya - Dadang Setiawan; Zainudin Zainudin; Aziz Hafidu; Mohammad Fahmi; Aries Saifudin; Yulianti Yulianti (Teknik Informatika Universitas Pamulang, 2022)
Income is a form of service that is given in an orderly manner to an employee for services and the results of his work. PT. Srikandhi Nusantara Jaya is an industry engaged in construction. With the information processing process that is still manual using the MS.Excel program, this leads to the formation of errors in calculating employee income, as well as the process of printing income slips which takes a long time. application is very meaningful to support the smooth payment of employee income. Therefore, a computerized data processing system is needed to meet the data needs of all those who need it and to prioritize the convenience of providing information quickly and accurately. ..The goal is to identify company issues related to the employee salary data system currently in operation. The current system processes employee information, which is done manually at the time of processing payroll. A web-based employee payroll information system will make it easier for companies to manage employee data for reporting and payroll purposes.When preparing monthly payroll, financial administrators must combine and separate payroll data for permanent and contract employees. This data is included in the monthly payroll report, so it is important to have a good digital management system in place so you can generate reports. This application was researched.